Adjuvant High-Definition Transcranial Direct Current Stimulation for Negative Symptoms in Schizophrenia: A Pilot Study. Issue 3 (September 2021) - Dharani, Ramamoorthy; Goyal, Nishant; Mukherjee, Aniruddha; Umesh, Shreekantiah
Abstract : Objective: In schizophrenia, negative symptoms account for a substantial amount of the comorbidity resulting in poor performance in social interaction, interpersonal relationships, economic functioning, and recreational activities. Research has implicated hypofrontality in the pathogenesis of negative symptoms of schizophrenia. Conventional transcranial direct current stimulation (tDCS) to the dorsolateral prefrontal cortex has attracted significant interest as an add-on treatment for negative symptoms in schizophrenia. High-definition tDCS (HD-tDCS), an optimized form of tDCS, has the potential for more focalized neuromodulation. Hence, we aimed to evaluate the efficacy of HD-tDCS over the left dorsolateral prefrontal cortex in the improvement of negative symptoms in schizophrenia. Methods: Fourteen patients with schizophrenia with predominantly negative symptoms were enrolled for this pilot, randomized, sham-controlled, double-blind trial. Each participant received 10 sessions of HD-tDCS at 2 mA for 20 minutes twice daily over 5 days. Negative symptoms were assessed with the Scale for Assessment of Negative Symptoms and Positive and Negative Syndrome Scale for Schizophrenia. The Calgary Depression Scale for Schizophrenia was used to rule out depressive symptoms. Assessments were carried out at baseline and at 2 weeks. Results: The improvement in negative symptoms in the active group was statistically significant at P value of 0.05 as compared with the sham group. Conclusion: These results suggest that HD-tDCS may lead to improvement in negative symptoms of schizophrenia. Its use as an adjunct to pharmacological treatment of negative symptoms may be worth considering.